The mental health of women facing maternity and career reconciliation in the time of the Covid-19 pandemic: a case study with health professionals (Research, Society and Development, 2022)
This work, funded by CAPES (Coordination for the Improvement of Higher Education Personnel), aimed to (re)think the mental health of working women/mothers in the face of the exercise of professional activities in a health context in the time of the Covid-19 pandemic, in addition to presenting and describing the meaning of the work for them. For that, the qualitative research method of the case study type was adopted. The study included 06 women, mothers and professionals working in the health area, linked to the public sector of a municipality located in the south of Minas Gerais. A semi-structured interview was used as a technique, data processing was based on Bardin's content analysis. The results were analyzed through the psychodynamics of work in dialogue with gender theories. As a result, it was understood that the combination of work and family is loaded with adversity for these women, but factors such as sharing care with the offspring, as well as household chores, reflect on a better quality of life for them, since contributes to a lower care burden. In this context, the professionals reported experiencing conflicts, such as the relationship with the partner, the scarcity of an effective support network and the physical and mental overload in the face of reconciling motherhood and professional career.